Section 8 Is the New N-Word: Policing Integration in the Age of Black Mobility - Norrinda Brown Hayat (Washington University Journal of Law & Policy, 2016)
This Article addresses the concept of black mobility within the context of Section 8 housing vouchers. Hayat explores the rise of racially coded language and its impact on racially discriminatory housing measures, highlighting the intersectionality between narratives of black criminality and the implicit biases of Section 8 proponents. Hayat argues for eradication of Section 8 enforcement schemes and facially race-neutral policies to promote the elimination of hyper-segregated neighborhoods.
Keywords: African-Americans; Section 8; Socio-economic status; housing; Fair Housing Act; Department of Housing and Urban Development; segregation; Black Mobility